Biochemical characterization of recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) protein from Leucaena leucocephala was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. Optimum pH for forward and reverse reaction was found to be 6.5 and 7.8 respectively. The enzyme was most stable around pH 6.5 at 25 degrees C for 90 min. The enzyme showed k(cat)/k(m) for feruloyl, caffeoyl, sinapoyl, coumaroyl CoA, coniferaldehyde and sinapaldehyde as 4.6, 2.4, 2.3, 1.7, 1.9 and 1.2 (x10(6) M-1 s(-1)), respectively, indicating affinity of enzyme for feruloyl CoA over other substrates and preference of reduction reaction over oxidation. Activation energy, E-a for various substrates was found to be in the range of 20-50 kJ/mol. Involvement of probable carboxylate ion, histidine, lysine or tyrosine at the active site of enzyme was predicted by pH activity profile. SAXS studies of protein showed radius 3.04 nm and volume 49.25 nm(3) with oblate ellipsoid shape. Finally, metal ion inhibition studies revealed that Ll-CCRH1 is a metal independent enzyme. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Activation energy; Cinnamoyl CoA esters; Cinnamoyl CoA reductase 1; SAXS; stability

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Sonawane, Prashant; Singh, Somesh; Kumari, Uma; Ruby; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2013)
Triterpenoid saponins are the class of secondary metabolites, synthesized via isoprenoid pathway. Oxidosqualene cyclases (OSCs) catalyzes the cyclization of 2, 3-oxidosqualene to various triterpene skeletons, the first committed step in triterpenoid biosynthesis. A full-length oxidosqualene cyclase cDNA from Bacopa monniera (BmOSC) was isolated and characterized. The open reading frame (ORF) of BmOSC consists of 2,292 bp, encoding 764 amino acid residues with an apparent molecular mass of 87.62 kDa and theoretical pI 6.21. It contained four QxxxxxW motifs, one Asp-Cys-Thr-Ala-Glu (DCTAE) motif which is highly conserved among the triterpene synthases and another MWCYCR motif involved in the formation of triterpenoid skeletons. The deduced amino acid sequence of BmOSC shares 80.5 % & 71.8 % identity and 89.7 % & 83.5 % similarity with Olea europaea mixed amyrin synthase and Panax notoginseng dammarenediol synthase respectively. Phylogenetic analysis revealed that BmOSC is closely related with other plant OSCs. Quantitative real-time PCR (qRT-PCR) data showed that BmOSC is expressed in all tissues examined with higher expression in stem and leaves as compared to roots and floral parts.

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection

Steady state fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1) and its active site mutants - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (Journal of Fluorescence, 2014)
Fluorescence quenching and time resolved fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1), a multitryptophan protein from Leucaena leucocephala and 10 different active site mutants were carried out to investigate tryptophan environment. The enzyme showed highest affinity for feruloyl CoA (K (a) = 3.72 x 10(5) M-1) over other CoA esters and cinnamaldehydes, as determined by fluorescence spectroscopy. Quenching of the fluorescence by acrylamide for wild type and active site mutants was collisional with almost 100 % of the tryptophan fluorescence accessible under native condition and remained same after denaturation of protein with 6 M GdnHCl. In wild type Ll-CCRH1, the extent of quenching achieved with iodide (f (a) = 1.0) was significantly higher than cesium ions (f (a) = 0.33) suggesting more density of positive charge around surface of trp conformers under native conditions. Denaturation of wild type protein with 6 M GdnHCl led to significant increase in the quenching with cesium (f (a) = 0.54), whereas quenching with iodide ion was decreased (f (a) = 0.78), indicating reorientation of charge density around trp from positive to negative and heterogeneity in trp environment. The Stern-Volmer plots for wild type and mutants Ll-CCRH1 under native and denatured conditions, with cesium ion yielded biphasic quenching profiles. The extent of quenching for cesium and iodide ions under native and denatured conditions observed in active site mutants was significantly different from wild type Ll-CCRH1 under the same conditions. Thus, single substitution type mutations of active site residues showed heterogeneity in tryptophan microenvironment and differential degree of conformation of protein under native or denatured conditions.
Keywords: Active site mutants; Cinnamoyl CoA reductase; fluorescence; Ligand binding; Solute quenching

Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase